PENGARUH HARGA DAN FASILITAS TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DI OBJEK WISATA BUKIT GIBEON KECAMATAN AJIBATA KABUPATEN TOBA SAMOSIR - Helena Sirait; Khafi Puddin (Jurnal PLANS : Penelitian Ilmu Manajemen dan Bisnis, 2018)
This study aims to determine and can explain the influence of price and facilities on Tourist Tourist Decision In Tourism Object Bukit Gibeon Ajibata District Toba Samosir. The population in this study is 143,769 tourists determined from the number of visitors Bukit Gibeon Tourism Object in the period of one year, and the sample used amounted to 100 visitors. Data analysis technique used is Multiple Linear Regression used questionnaires by distributing questionnaires to samples (respondents) and collecting them back for processing. Data analysis technique used is data quality test and classical assumption test. Hypothesis testing using multiple linear regression analysis, T test, F test, and R2 test. Data analysis of each variable is obtained by multiple regression equation Y = 4,202 + 0,320 X1 + 0,652 X2 + e. Obtained R2 equal to 0,349 which mean X1 and X2 explain influence to variable Y equal to 34,9% while rest 65,1% explained variable outside company. The partial test resulted by each independent variable has an effect on the dependent variable with the research significance is smaller than 0.05, and the result of simultaneous-test calculation is 26,024 with F table 3.09 which means F count > F table with level of significant (α) < 0.05, which means the accepted hypothesis that Price and Facilities together have a significant effect on Tourist Visits Decision. Thus it can be concluded that Price and Facilities have a positive effect on Tourist Visits Decision In Tourism Object Gibeon Bukit Ajibata District Toba Samosir. Keywords: Price, Facilities, and Tourist Visiting Decision